TRC4 Gene Based Pcr Assay in Diagnosis Of Extrapulmonary Tuberculosis - Setu, Sanjida Khondakar; Ahmed, Sarmin; Sattar, Abu Naser Ibn; Firoz, Md Towfique Hasan; Hasan, Md Kamrul; Sumon, Mostofa Aziz (Journal of Chittagong Medical College Teachers’ Association, 2014)
Diagnosis of Extra-pulmonary tuberculosis (EPTB) is challenging due to atypical presentation and various inadequacies of diagnostic tools. This study aimed to evaluate polymerase chain reaction (PCR) assay by using TRC4 primers in comparison with the IS6110 primers to detect Mycobacterium tuberculosis from extra pulmonary samples. This study was done in Microbiology and Immunology Department of BSMMU from 162 extra-pulmonary samples sent for laboratory investigation of M. tuberculosis during the period of March 2013 to February 2014. All patients were subjected to AFB smear by Z-N staining, culture in L-J media and PCR by two primes IS6110 and TRC4. Among EPTB cases 24 (25.26%) were positive by AFB smear and/or mycobacterial culture and 73(76.84%) cases were positive by PCR test. PCR showed significantly higher detection rate of EPTB cases than that of AFB smear and L-J medium culture (p <0.005). Only IS6110 and only TRC4 were positive in 4.1% and 12.5% cases respectively. The sensitivity of PCR using TRC4 primers was higher (85.71%) than IS6110 primers (80.95%). Repetitive elements TRC4 can be an ideal target for PCR assays to identify M. tuberculosis; in strains carrying no copies or single copy of 156110 and can play a significant role in diagnose the EPTB cases. JCMCTA 2014 ; 25 (1): 12-17